The quality of life of breast cancer female patients in Montenegro - Pelicic, Damir; Saveljic, Mitar; Vukcevic, Batric; Miljanovic, Gora (Acta medicae Medianae, 2021)
Introduction/Aims: Breast cancer is a common malignant disease in the Balkan region. The aim was to determine whether there is a difference in the parameters of perception of health and quality of life in Montenegrin female patients after surgery, chemotherapy and radiation therapy for breast cancer in relation to age, the type of treatment, and the attitudes towards preventive diagnostic measures. Methods: The research was carried out on a sample of 200 women diagnosed with breast cancer in health institutions in Montenegro. Authentically designed questionnaire relying on three questionnaires (Functional Assesment of Cancer Therapy: General (FACT-G), its breast cancer-specific type (FACT-B), and the instrument designed by the European Organisation for Research and Treatment of Cancer (EORTC-QLQ C30)) was used. Results:The lowest quality of life was seen in patients aged 60 – 64 years. The patients frequently reported that they feel sad, lose hope or worry about family members suffering from breast cancer. The quality of life was lower in patients who stated that they do not understand their disease well. Conclusion: These results should inspire the clinicians to educate the patients and to provide psychological support during the treatment.